2021
DOI: 10.3390/pharmaceutics13071101
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Networks to Predict the Intrinsic Solubility of Drug-Like Molecules

Abstract: Machine learning (ML) approaches are receiving increasing attention from pharmaceutical companies and regulatory agencies, given their ability to mine knowledge from available data. In drug discovery, for example, they are employed in quantitative structure–property relationship (QSPR) models to predict biological properties from the chemical structure of a drug molecule. In this paper, following the Second Solubility Challenge (SC-2), a QSPR model based on artificial neural networks (ANNs) was built to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Tight and loose test sets from SC2019 have been independently used four times to test new and existing models [ 20 , 27 , 28 , 29 ]. Avdeef [ 20 ] has collected aqueous solubility data from 1325 literature sources (multi-source compilations, single-source measurements for many compounds, and miscellaneous primary sources) and curated and analyzed this data to obtain 6355 intrinsic aqueous solubility values for 3014 different chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tight and loose test sets from SC2019 have been independently used four times to test new and existing models [ 20 , 27 , 28 , 29 ]. Avdeef [ 20 ] has collected aqueous solubility data from 1325 literature sources (multi-source compilations, single-source measurements for many compounds, and miscellaneous primary sources) and curated and analyzed this data to obtain 6355 intrinsic aqueous solubility values for 3014 different chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…They found that despite their training set having inconsistencies related to pH, solid form, and temperature, the developed model had comparable prediction capability to the top-ranked models in SC2019. Tosca et al [ 28 ] developed an artificial neural networks QSPR model for intrinsic aqueous solubility and predicted both test sets with a sufficient prediction accuracy. Francoeur and Koes [ 29 ] used molecule attention transformer (MAT) architecture to develop a model (called SolTranNet) for data from AqSolDB.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noticed for long that clinical application of many potent remedial drugs in cancer and other diseases have been limited due to the following reasons: 1) poor aqueous solubility, and consequently, minimal systemic bioavailability (Anitha et al, 2011;Tosca et al, 2021). During the treatment, patients need to be injected with a large amount of saline, which easily causes water intoxication (Lauersen and Birnbaum, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, interest regarding the use of ML algorithms across diverse disciplines in pharmaceutical design and development has grown [ 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. While ML models have been produced to optimise lipid-based formulation (LBF) development [ 3 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the application of more novel ML approaches for bio-enabling formulations currently focuses on solid dispersions (SDs) [ 21 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%